Coupled continuum pipe-flow modeling of Karst groundwater flow in the Madison limestone aquifer, South Dakota - Saller, Stephen Paul, author; Ronayne, Michael, advisor; Sale, Thomas, committee member; Egenhoff, Sven, committee member (Colorado State University. Libraries, 2013)
Karst carbonate aquifers are traditionally difficult to model due to extreme permeability heterogeneities and non-Darcian flow. New modeling techniques and test applications are needed to improve simulation capabilities for these complex groundwater systems. This study evaluates the coupled continuum pipe-flow framework for modeling groundwater flow in the Madison aquifer near Rapid City, South Dakota. The Madison carbonate formation is an important source of groundwater underlying Rapid City. An existing equivalent porous medium (EPM) groundwater model of the Madison aquifer was modified to include pipe networks representing conduits. In the EPM model, karstified portions of the aquifer are modeled using high hydraulic conductivity zones. This study hypothesized that the inclusion of conduits would allow for a simpler hydraulic conductivity distribution and would improve modeled fits to available data from a 10-year monitoring period. Conduit networks were iteratively fit into the model based upon available environmental and dye tracer test data that approximated major karst pathways. Transient simulation results were evaluated using observation well hydraulic heads and estimated springflow data. In a comparison to the EPM model, the new modeling results show an improved fit to the majority of observation well targets, and negligible impact to springflow data. The flow dynamics of the aquifer model were significantly altered, with the conduit networks acting as gaining or losing subsurface features, behaving as regional sinks during dry periods and flowpath heterogeneities during wet periods. The results of this study demonstrate that the coupled continuum pipe-flow modeling method is viable for use within large regional aquifer models.
Keywords: groundwater; modeling; karst; hydrogeology; CFP; conduit